Peran LSM dalam Mendukung Anak-Anak Korban Kekerasan - Nur Azizah, Nur Azizah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2024)
This article discusses the role of Non-Governmental Organizations (NGOs) in supporting children victims of violence through a variety of programs that include psychosocial support, education, and skills development. This research reveals the main challenges faced by NGOs, such as limited funds and human resources, as well as a lack of public awareness. Despite facing many obstacles, NGOs have shown tremendous dedication in helping children recover from trauma and rebuild their lives. The study also provides recommendations to improve the effectiveness of NGO programs through greater support from the government and the community. With the right support, NGOs can continue to provide much-needed services and have a positive impact on children victims of violence.